New therapeutic targets and mechanisms of papillary thyroid carcinoma identified by multi-omics analysis - Jianxiong Xu; Chen Gao (Discover Oncology)
Abstract Introduction The treatment of papillary thyroid carcinoma (PTC) presents ongoing challenges, underscoring the need for novel therapeutic targets. Methods This study employed proteomic MR analysis, utilizing publicly available data from genome-wide association studies (GWAS) and protein quantitative trait loci (pQTL) studies. We analyzed proteomic data from deCODE and the UK Biobank Protein Project (UKB-PP), along with GWAS data on papillary thyroid carcinoma (PTC) from the Finnish Consortium. This analysis was further supported by eQTL validation and bioinformatics differential analysis to identify potential therapeutic targets for PTC. Additionally, we explored possible downstream mechanisms of the target proteins through mediation analysis. Results Our analysis identified two potential therapeutic targets associated with PTC, specifically, LY75 and S100A12. Mediation analysis further investigated their potential mechanistic role in the pathogenesis of PTC. Conclusion Through multi-omics analysis, we identified new potential therapeutic targets for papillary thyroid carcinoma and investigated their possible underlying mechanisms affecting PTC.